Goal pursuit, goal attainment and subjective well-being among young adults and the elderly of India: A mixed method study - Ookken, Lis Johnny (Animo Repository, 2015)
The current study, using a sequential explanatory mixed method design, at first examined the effect of independent goal pursuit, interdependent goal pursuit, independent goal attainment, interdependent goal attainment on subjective well-being, and the potential moderation of developmental level (young adulthood and late adulthood) in all these effects. The participants of the quantitative study composed of 186 young adults and 146 elderly. The multiple regression analysis was used to test the eight hypotheses of the study. The results of the quantitative study were 1. The interdependent goal attainment predicted SWL, 2. The relationship between the interdependent goal attainment and SWL was moderated by the developmental level, 3. Independent goal attainment predicted SWB, 4. The relationship between independent goal attainment and SWB was not moderated by developmental levels, 5. Goal pursuit (both independent and interdependent) is not a significant predictor of SWB. The most important finding in the quantitative phase was that the interdependent goal attainment predicted SWL and was moderated by the developmental level. The impact of the relationship between interdependent goal attainment and life satisfaction was more significant for the elderly than for the young adults. Seeking an explanation for the most important finding in the quantitative phase, the researcher did a qualitative study. This helped to gain a deeper understanding of the process of the Indian young adults and the elderlys attainment of goals in relation to their happiness. In the qualitative phase, researcher conducted in-depth interviews of ten young adults and ten elderly people who were selected based on the highest and lowest scores of SWB. The results explained how the reasons were different among the young adults and the elderly for their interdependent goal attainment on life satisfaction. The implications of the new findings for the counseling practice and for the future research were discussed.